The effectiveness of problem-based learning in the web-based environment for the delivery an undergraduate physics course - Hanafi Atan; Fauziah Sulaiman; Rozhan M Idrus (2005)
This paper reports the investigation of the effectiveness of Problem-Based Learning (PBL) within a web-based environment in the delivery of an undergraduate Physics course. The effectiveness was evaluated by comparing the performances and the perceptions of the sample students (n=67) using the web-based PBL and comparing the outcomes with those of the web-based Content-Based Learning (CBL). The comparative post-test performance analysis conducted using a student t-test statistical analysis (p<0.05) revealed that the experimental web-based PBL approach yielded better performances than the controlled CBL approach. Where perceptions were concerned, the analysis also revealed that students exposed to the web-based PBL approach responded more positively with their knowledge enhancement compared to students exposed to the web-based CBL approach.